Intra-peritoneal mature benign cystic teratoma deposits: an unusual complication from previous surgical resection of an ovarian mature benign cystic teratoma - Prasad, Radhika (BJR Case Rep, 2018)
In this case, we describe multiple unusual intra-peritoneal lesions containing fat, soft tissue and calcification. These were found radiologically and histologically to be in keeping with mature benign cystic teratoma intra-peritoneal deposits, also described as dermoid cysts. These were presumed to be due to seeding from surgical resection of ovarian mature benign cystic teratoma 5 years previously. This surgical complication has not been well documented thus far in the literature.